1996
DOI: 10.1111/j.1468-1331.1996.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuropathy and anti‐Hu antibodies in a patient with seminoma

Abstract: A man with subacute sensory ncuronopathy (SSN) had a stage 1 seminoma. His serum and cerebrospinal fluid (CSF) contained anti‐Hu antibodies (type 1 anti‐neuronal nuclear antibodies, ANNA‐1). Following orchidectomy, radiotherapy, prednisolone, plasma exchange and intravenous immunoglobulin the antineuronal antibody titre fell and the neuropathy improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…The fact that serum titres of antineuronal Ab dropped substantially in six out of the seven patients in whom we obtained serum samples before and after treatment, including three patients who received immunosuppressors alone, could favour the hypothesis of a real beneficial effect of immunosuppressors. Nevertheless, such findings have been made previously after plasmapheresis or IVIg without a clinical counterpart7 8 25 and we were not able, as others,1 2 5 26 to find a correlation between serum titres of Ab and neurological course. For example, patient 1 who experienced “useful” stabilisation had a 10-fold fall in serum titre after treatment but patient 4 also had a striking drop of serum Ab (16-fold) despite progressive neurological deterioration.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The fact that serum titres of antineuronal Ab dropped substantially in six out of the seven patients in whom we obtained serum samples before and after treatment, including three patients who received immunosuppressors alone, could favour the hypothesis of a real beneficial effect of immunosuppressors. Nevertheless, such findings have been made previously after plasmapheresis or IVIg without a clinical counterpart7 8 25 and we were not able, as others,1 2 5 26 to find a correlation between serum titres of Ab and neurological course. For example, patient 1 who experienced “useful” stabilisation had a 10-fold fall in serum titre after treatment but patient 4 also had a striking drop of serum Ab (16-fold) despite progressive neurological deterioration.…”
Section: Discussioncontrasting
confidence: 75%
“…In a previous study we also found that a few patients with SN (two of six with RS⩽3) apparently benefited from IVIg 8. It is of interest to note that five out of the six patients with an anti-Hu syndrome who have been reported to improve after various immunosuppressors (and antitumour treatment in five cases) had an exclusive involvement of the peripheral nervous system with sensory neuropathy as the main finding,1-3 5 6 8leading to the suggestion that the lack of a blood-brain or blood-nerve barrier at the level of the dorsal root ganglia could facilitate the entry and action of immunosuppressors in patients with SN. The second possibility is that our three patients had an indolent form of the disease24 or had a spontaneous stabilisation, an issue that we identified in previous studies 8.…”
Section: Discussionmentioning
confidence: 80%
“…Gabriel et al reported 1 patient with seminoma and anti-Hu-associated PSN who achieved sustained im-provement with orchidectomy, radiation therapy, prednisone, a course of plasma exchange, and IVIg (total dose 115 g). 8 In this case, prednisone therapy for 5 weeks after orchidectomy followed by radiation therapy did not bring any clinical improvement, but 1 month after one course of plasma exchange and one course of IVIg, neuropathic symptoms began to improve and continued to improve over a 1-year period. They suggested that vigorous treatment of an underlying neoplasm and reduction of the titer of antineuronal antibodies are appropriate goals in the treatment of PSN.…”
Section: Discussionmentioning
confidence: 58%
“…3,9 The investigators postulated that the poor outcome in PSN could be ascribed to irreversible neuronal damage which had already occurred before the treatment was started, 3 and to therapeutic failure to effect an intrathecal immune response. 8 Since our abstract reported case 1 in 1990, 17 7 cases of anti-Hu-associated PSN showing clinical improvement with immunotherapies and anticancer therapy have been described (Table 2). 1,8,20,22,23 In 1 patient with anti-Hu-associated PVN, chemotherapy for cancer alone induced clinical improvement of mononeuropathy multiplex and a decrease of the anti-Hu antibody titer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation